Paradoxical Effect of TrkA Inhibition in Alzheimer’s Disease Models - Zhang, Qiang (2014)
An unbiased screen for compounds that block amyloid-β protein precursor (AβPP) caspase cleavage identified ADDN-1351, which reduced AβPP-C31 by 90%. Target identification studies showed that ADDN-1351 is a TrkA inhibitor, and, in complementary studies, TrkA overexpression increased AβPP-C31 and cell death. TrkA was shown to interact with AβPP and suppress AβPP-mediated transcriptional activation. Moreover, treatment of PDAPP transgenic mice with the known TrkA inhibitor GW441756 increased sAβPPα and the sAβPPα to Aβ ratio. These results suggest TrkA inhibition—rather than NGF activation—as a novel therapeutic approach, and raise the possibility that such an approach may counteract the hyperactive signaling resulting from the accumulation of active NGF-TrkA complexes due to reduced retrograde transport. The results also suggest that one component of an optimal therapy for Alzheimer’s disease may be a TrkA inhibitor.